Immunotherapy for extensive stage small cell lung cancer - Pacheco, Jose M. (J Thorac Dis, 2020)
Small cell lung cancer (SCLC) is an aggressive malignancy. Until recently the standard of care for newly diagnosed patients with extensive-stage disease was chemotherapy consisting of etoposide plus a platinum (EP). The median overall survival (OS) was only about 10 months with this systemic therapy. Immune checkpoint inhibitors were first evaluated as second or subsequent line treatments in extensive stage disease and later in combination with EP in the first-line setting. Recently two randomized phase III trials have demonstrated statistically improved OS with addition of a programmed death ligand-1 (PD-L1) inhibitor to EP. As a result, the standard of care for newly diagnosed patients with extensive-stage SCLC has changed for the first time in decades. However, many patients do not derive benefit from the addition of a PD-L1 inhibitor to EP. In this review we discuss first-line trials of chemoimmunotherapy in extensive stage SCLC and summarize data on second and subsequent line treatment with immune checkpoint inhibitors in immunotherapy-naïve patients. Additionally, we discuss potential biomarkers that could be utilized to select for which patients derive benefit from addition of a PD-L1 inhibitor to EP and propose ways to improve on first-line chemoimmunotherapy.